(untitled) (مجلة إحالات, 2026)
This study aims at highlighting the nature of Algerian theatre discourse through its long history starting from the 1970’s to the third millennium. Our main purpose is to tackle the nature of the discourse used in the majority of Algerian theatrical texts. Such study paves the way to a thorough knowledge of these discourses as well as comparing it to the nature of the period in which it was produced. Further, the study aims at portraying a global idea about the main discourses tackled by Algerian theatre in its different periods.